2022
DOI: 10.1111/aji.13590
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and inflammatory immune responses: Indian experience

Abstract: Endometriosis is a public health disorder affecting ∼ 247 million women globally and ∼ 42 million women in India. Women with endometriosis suffer from dysmenorrhea, chronic pelvic pain, dyspareunia, dyschezia, fatigue, depression, and infertility leading to significant socioeconomic impact and morbidity. The etiology of endometriosis is not understood well even after 100 years of research. Currently, there is no permanent cure for endometriosis. The inflammatory immune response is one of the important features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 122 publications
0
22
0
Order By: Relevance
“…This makes one wonder why some people are normal and others have endometriosis. Some studies have shown that the immune system's failure to clear the ectopic endometrium in time or its failure to clear it is also one of the important causes of endometriosis [22,23]. It has been found that the expression of the anti-apoptotic genes is up-regulated in the eutopic and ectopic endometrium of patients with endometriosis, which proves that there is an anti-apoptotic phenomenon in endometriosis [24].…”
Section: Endometriosis Pathophysiologymentioning
confidence: 98%
“…This makes one wonder why some people are normal and others have endometriosis. Some studies have shown that the immune system's failure to clear the ectopic endometrium in time or its failure to clear it is also one of the important causes of endometriosis [22,23]. It has been found that the expression of the anti-apoptotic genes is up-regulated in the eutopic and ectopic endometrium of patients with endometriosis, which proves that there is an anti-apoptotic phenomenon in endometriosis [24].…”
Section: Endometriosis Pathophysiologymentioning
confidence: 98%
“…11 Gajbhiye R. reviewed their group's experiences of the inflammatory immune response, autoimmunity, comorbidities and clinical phenotypes in Indian women with endometriosis. 12 Their investigations revealed presence of anti-endometrial antibodies (AEAs) in Indian women with endometriosis that are majorly targeting tropomyosin 3, stomatin-like protein2 and tropomodulin 3. necrosis factor along with the promising novel immunomodulatory therapies. 14 The role of immune dysregulation in male infertility is an area relatively less researched.…”
Section: Infertility: Autoimmunity Infection and Immune Dysregulationmentioning
confidence: 99%
“…Pires and Parikh have reviewed the literature on the relevance and efficacy of immunoassays for anti‐ovarian antibodies including their own efforts to identify the cause and a method to overcome non‐specificity in these immunoassays 11 . Gajbhiye R. reviewed their group's experiences of the inflammatory immune response, autoimmunity, comorbidities and clinical phenotypes in Indian women with endometriosis 12 . Their investigations revealed presence of anti‐endometrial antibodies (AEAs) in Indian women with endometriosis that are majorly targeting tropomyosin 3, stomatin‐like protein2 and tropomodulin 3.…”
Section: Infertility: Autoimmunity Infection and Immune Dysregulationmentioning
confidence: 99%
“…Endometriosis is a benign estrogen-dependent chronic systemic inflammatory gynecological condition with multifactorial etiopathogenesis. The disease is characterized by the presence of actively functioning foci of endometrium (glandular cells and stroma) or endometrial tissue outside the uterine cavity, i.e., in the muscular layer of the uterine wall or in the other organs of reproductive system, or/and in the adjacent or distant structures [1][2][3]. Being a common gynecologic disease, endometriosis occurs in 10-15% of women of reproductive age, including 35-50% of women with pelvic pain and/or infertility [1].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis often leads to chronic pelvic pain, dysmenorrhea, dyspareunia, infertility, and impaired quality of life, significantly burdening health in general [2,3], as confirmed by reliable special questionnaires [5], and represents a serious medical and socioeconomic problem. The lack of specific signs and symptoms makes accurate diagnosis a major challenge.…”
Section: Introductionmentioning
confidence: 99%